Interaction of nitric oxide and cyclic guanosine 3',5'-monophosphate in erythropoietin production. - Ohigashi, T (1993)
The present study was designed to investigate whether in vivo and in vitro erythropoietin (EPO) production is modulated by nitric oxide (NO) and cyclic guanosine 3',5'-monophosphate (cGMP). Serum levels of EPO in ex-hypoxic polycythemic mice were significantly increased after injections of 200 micrograms/kg sodium nitroprusside for 4 d. One injection of NG-nitro-L-arginine methyl ester (L-NAME) produced a significant dose-related decrease in serum levels of EPO in ex-hypoxic polycythemic mice in response to hypoxia. When EPO producing Hep3B cells were incubated in 1% O2 for 30 min, cGMP levels in the Hep3B cells were significantly elevated, compared with cells incubated in 20% O2. The elevation of cGMP by hypoxia was inhibited by L-NAME (100 microM). Sodium nitroprusside (10 and 100 microM) and NO (2 microM) also significantly increased cGMP levels in Hep3B cells. L-NAME, LY 83583 (6-Anilino-5,8-quinolinedione, a soluble guanylate cyclase inhibitor), and Rp-8-Bromo-cGMPS (Rp-8-Bromo-guanosine 3',5'-cyclic monophosphothioate, a cGMP-dependent protein kinase inhibitor) significantly inhibited the hypoxia-induced increase in medium levels of EPO in Hep3B cells. 8-Bromo-cGMPS produced a dose-dependent decrease in EPO messenger RNA levels in Hep3B cells in response to hypoxia. 8-Bromo-cGMP (10(-3) M) produced significant increases in medium levels of EPO in Hep3B cell cultures incubated under normoxic conditions, which was enhanced by the phosphodiesterase inhibitor, 3-isobutyl-1-methylxanthine (0.2 mM). These results suggest that NO and cGMP may interact in modulating hypoxic stimulation of EPO production.